2023
DOI: 10.1200/op.22.00736
|View full text |Cite
|
Sign up to set email alerts
|

Profile of the Postoperative Care Provided for Patients With Pancreatic and Periampullary Cancers by Family and Unpaid Caregivers

Abstract: PURPOSE Patients with pancreatic and periampullary cancers may experience significant reduction in their quality of life and often rely on family and unpaid caregivers for assistance after surgery. However, as caregivers are not systematically identified, little is known about the nature, difficulty, and personal demands of assistance they provide. We aim to assess the frequency and difficulty of specific assistance caregivers provide and identify potential interventions that could alleviate the caregiving dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…[17][18][19] In fact, a study by Engebretson et al 20 found that almost half of pancreatic cancer caregivers had to quit their job to care for their loved one. There were similar indications from the qualitative portion of Fong et al 8 such that caregivers struggled with understanding billing and preparing financially for the level of care required. With this, tailoring support to consider the distinct needs of different at-risk caregivers across the disease trajectory and across multiple domains of functioning is ideal-not only for the well-being of the caregiver but also for the well-being of the patient.…”
mentioning
confidence: 67%
See 4 more Smart Citations
“…[17][18][19] In fact, a study by Engebretson et al 20 found that almost half of pancreatic cancer caregivers had to quit their job to care for their loved one. There were similar indications from the qualitative portion of Fong et al 8 such that caregivers struggled with understanding billing and preparing financially for the level of care required. With this, tailoring support to consider the distinct needs of different at-risk caregivers across the disease trajectory and across multiple domains of functioning is ideal-not only for the well-being of the caregiver but also for the well-being of the patient.…”
mentioning
confidence: 67%
“…The age composition of the sample in the study of Fong et al 8 highlights the growing trend of young adult caregivers: 26% of the study's sample were the adult child of the patient, and 22% had at least one child of their own younger than 18 years. These young adult caregivers must integrate their career with other care responsibilities and are at a much greater risk of financial toxicity than older adult caregivers.…”
mentioning
confidence: 95%
See 3 more Smart Citations